2001
DOI: 10.1056/nejm200107193450301
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer after Prophylactic Bilateral Mastectomy in Women with aBRCA1orBRCA2Mutation

Abstract: In women with a BRCA1 or BRCA2 mutation, prophylactic bilateral total mastectomy reduces the incidence of breast cancer at three years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
378
4
29

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 882 publications
(426 citation statements)
references
References 32 publications
(39 reference statements)
15
378
4
29
Order By: Relevance
“…Two recent studies involving BRCA mutation carriers demonstrated similar findings. Meijers-Heijboer et al 6 found that 50% of BRCA mutation carriers (4 of 8) who chose to undergo close surveillance rather than prophylactic mastectomy developed interval breast carcinoma; these interval malignancies were discovered 2-5 months after normal findings were noted on screening mammography. Similarly, Scheuer et al 11 reported that 6 of 12 patients (50%) developed interval breast carcinoma, which became evident 6 -10 months after normal findings were observed on screening mammography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies involving BRCA mutation carriers demonstrated similar findings. Meijers-Heijboer et al 6 found that 50% of BRCA mutation carriers (4 of 8) who chose to undergo close surveillance rather than prophylactic mastectomy developed interval breast carcinoma; these interval malignancies were discovered 2-5 months after normal findings were noted on screening mammography. Similarly, Scheuer et al 11 reported that 6 of 12 patients (50%) developed interval breast carcinoma, which became evident 6 -10 months after normal findings were observed on screening mammography.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 Nonetheless, in spite of the debate regarding survival benefit, widespread adoption of the published breast carcinoma screening guidelines has led to earlier detection of breast malignancies and to the detection of a larger proportion of these malignancies in a noninvasive stage. 6,7 Over the last decade, with the advent of genetic testing, two major genes associated with increased susceptibility to breast carcinoma-breast cancer susceptibility gene 1 (BRCA1) and breast cancer susceptibility gene 2 (BRCA2)-have been identified. Mutations in these genes confer a 60 -85% lifetime risk of developing breast carcinoma.…”
mentioning
confidence: 99%
“…Identification of these individuals before they present with cancer is important since prophylactic surgery can reduce morbidity and mortality in these individuals (Struewing et al, 1995;Rebbeck et al, 1999;Hartmann et al, 1999;Hartmann et al, 2001;Meijers-Heijboer et al, 2001;Kauff et al, 2002;Rebbeck et al, 2004). Unfortunately, genetic testing is expensive, family history of breast cancer is common and BRCA mutations are rare (Ford et al, 1994;Peto et al, 1999;Antoniou et al, 2002).…”
mentioning
confidence: 99%
“…Some asymptomatic women carrying germline mutations in BRCA1 or BRCA2 genes undergo prophylactic bilateral mastectomy and/or salpingo-oophorectomy to reduce their risk of developing breast and/or ovarian cancer (Meijers-Heijboer et al, 2001;Stefanek et al, 2001;Rebbeck et al, 2002). Others are offered periodic clinical examination and breast imaging (mammography, ultrasound and magnetic resonance imaging).…”
mentioning
confidence: 99%